Application of liquid-infused membranes to mitigate biofouling. Issue 1 (29th September 2020) - Bazyar, Hanieh; Xu, Linya; de Vries, Hendrik Jan; Porada, Slawomir; Lammertink, Rob G. H.
Abstract : The novel liquid-infused membranes have been shown to mitigate membrane biofouling. Here, the long-term stability of these membrane have been tested and analyzed using bacterial growth curve models. Abstract : Among different types of membrane fouling, biofouling is a critical issue which can significantly reduce the process productivity. If the initial phase of the microorganism attachment to the pore wall is prevented, a remarkable reduction in biofilm formation can be obtained. A novel approach to achieve this goal is the infusion of the porous membrane with an infusion liquid (oil) forming liquid-infused membranes (LIMs). It has been shown that the pore wall during permeation is still covered with the infusion liquid forming so-called liquid-lined pores. The liquid-lining can enhance anti-biofouling performance by preventing direct contact between the microorganisms and pore wall. Here, we investigate the capability of LIMs in mitigation of biofouling by conducting long-term cross-flow filtration experiments at constant flow rate for approximately 10–20 days. The results show significantly lower increase in transmembrane pressure (TMP) values for LIMs compared to non-infused counterparts (dry membranes). The bacterial growth curves are further investigated by fitting a sigmoidal function (logistic model). Approximately 4 times increase in the lag period λ and 7 times decrease in the bacterial growth rate μ m are observed for LIMs compared to dry membranes revealing improved anti-biofouling performance of LIMs.